THE INFLUENCE OF ORGANIZATIONAL COMMITMENT AND JOB STRESS TOWARD JOB SATISFACTION OF EMPLOYEES FORTUNA MOTOR SEKADAU - Wulandari, Yola B1024141021 (Jurnal Manajemen Update, 2019)
Â ABSTRACTThe Influence ofÂ  Organizational Commitment and Job StressÂ  Toward Job Satisfaction of Employees Fortuna Motor SekadauBy:Yola WulandariB1024141021Â Â Â Â Â Â Â Â Â Â Â Â  The importance of employee job satisfaction in its work greatly affects the output of its work and also for the company. Job satisfaction is a problem that is most interesting and important because it has proven to be of great benefit to the interests of individuals, companies or organizations. This research was conducted with the aim to find out the effect of Organizational Commitment and Job Stress Impacts on Fortuna Motor Sekadau Employee Job Satisfaction and analyze how much influence the Effect of Organizational Commitment and Job Stress Influence on Job Satisfaction of Fortuna Motor Sekadau Employees. This research was conducted at a company engaged in the sale of motorized vehicles Fortuna Motor Sekadau, Jl. Merdeka Timur, Mungguk, Sekadau Hilir, Sekadau Regency, West Borneo. The population in this study were all employees Fortuna Motor Sekadau 86 people. The sampling method uses census techniques so that the number of samples used is 86 people. Research data collection using a questionnaire which will then be analyzed using the multiple linear regression method to test between independent variables and dependent variables. Based on research results, it can be seen that organizational commitment has a significant effect on employee job satisfaction, while job stress has no significant effect on job satisfaction.Keywords: Organizational Commitment, Job Stress, Job SatisfactionÂ Â Â Â Â Â Â Â Â Â Â REFERENCEÂ Akhtar. (2018). A study of Impact of Job Stress on Employeesâ€™Job Satisfaction: An Empirical Study of Private Banksof Pakistan.AllenÂ Â  andÂ Â  Meyer.Â Â  2013. TheÂ Â  MeasurementÂ Â  andÂ Â  AntecedentsÂ Â  ofÂ Â  Affective, Contintinuance and NormativeCommitment to Organitazion.PT Elex Media Komputindo, Jakarta.Allen, N. & Meyer, J.Â Â  (1990).Â Â Â  TheÂ  measurementÂ  andÂ  antecedents of affective,Â  continuanceÂ  andÂ  normativeÂ  commitmentÂ  toÂ  the organization.Â  Journal of Occupational Psychology, 63: 1-18.Al-Hussami, M., Nasar, M., Hussien, R. and Mahadeen, A. (2011), â€œPredictors of nursing faulty membersâ€™ organizational commitment in public universitiesâ€, Journal of Nursing Management, Vol. 19 No. 4, pp. 556-566.Bagraim, J. (2010). The dimensionality of workplace interpersonal trust and relationship to workplace affective commitment. Journal of industry phychology 33: 43-48.Cenzo, D. A., & Robbins, S. P. (2010). Fundamental of Human Resource Management. Hoboken: John Wiley & Sons, Inc.Cherian, S., Alkhatib, A. J., & Aggarwal, M. (2018). Relationship Between Organizational Commitment and Job Satisfaction of Nurses in Dubai Hospital.Chordiya, R., Sabharwal, M., Goodman, D. (2017) The Affective Organizational Commitment And Job Satisfaction: A Cross-National Comparative Study.Cooper, D., & Emory, D. (2002). Business Research Methode, 5th Edition. Chicago: Richard D. Irwin Inc.Dugguh & Dennis. (2014) The affective event theory 132-143.Ghozali,Â  Imam,Â  2013, AplikasiÂ  AnalisisÂ  MultivariateÂ  DenganÂ  ProgramÂ  IBMÂ  SPSSÂ  19Â  (edisikelima), Semarang: Universitas Diponegoro.Greener, S. (2008). Business Research Method. Bookbon.com.Inanca, E. E. & Ozdilek, E. (2015). Relationship between the organizational commitment and job satisfaction of academic staff in Turkey.John R. Schermerhorn, J., Hunt, J. G., & Osborn, R. N. (n.d.). Organizational Behavior Seventh Edition. Wiley.Karunanithy, K., & Ponnampalam, A. (2013). A study on the effect of Stress on performance of employees in Commercial Bank of Ceylon in the Eastern Province . European Journal of Business and Management Vol.5, No.27.Kasmadi, & Sunariah, N. S. (2014). Panduan Modern Penelitian Kuantitatif. Bandung: Alfabeta.Ketchland, A., & Strawser, J. (1998). The existence of multiple measures of organizatinal commitment and experienced related differences in a public accounting setting. Behavioral research in Accounting 10, 109-137.Khuzaeni. (2013). A Study of The Influence of Work Culture, Work Stress to the Job Satisfaction and Employees Performance in the State Treasury Service Office in Jakarta, Indonesia.Luthans, F. (2011). Organizational Behavior An Evidence-Based Approach 12th Edition. NewYork: Mc Graw-Hill.Mansoor, M., Fida, S., Nasir, S., & Ahmad, Z. (2011). The Impact of Job Stress on Employee Job Satisfaction A Study on Telecommunication Sector of Pakistan. Journal of Business Studies Quarterly , Vol. 2, No. 3, 50-56.Markovits Yannis, Davis Ann J. & Dick Rolf van (2007), â€œOrganizationalÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Commitment Profiles and Job Satisfaction among Greek Private andÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Public Sector Employeesâ€, International Journal of Cross CulturalÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Management, Vol. 7(1)Mathis, R. L., & Jackson, J. H. (2006). Human Resource Management THIRTEENTH EDITION. South-Western Cengage Learning.Meyer, J.Â  & Allen, N.Â Â Â  (1993).Â Â  â€œA threeÂ  component conceptualization ofÂ  organizationalÂ  commitmentâ€,Â  HumanÂ  Resource Management Review, 1:61-89Meyer, J. & Allen, N.Â Â  (1996).Â  Commitment in the Workplace: Theory, Research and Application.Â  London: Sage.Meyer, J. P., Stanley, D.Â  J., Herscovitch, L., &Topolnytsky, L.Â  (2002).Â  Affective,Â  continuanceÂ  andÂ  normativeÂ  commitmentÂ  toÂ  the organization:Â  A meta-analysis of antecedents,Â  correlates, and consequences.Â  Journal of Vocational Behavior, 61, 20-52Mullin, Laurie, J. (2002). Management and Organisational Behavior: 6th edition, 282.Nagori. (2019). Study of Relationship between Job Stress and Job Satisfaction in Print Media.Noe, R. A., Hollenbeck, J. R., Gerhart, B., & Wright, P. M. (2011). Fundamental of Human Resource Management. NewYork: McGraw-Hill/Irwin.Noor & Juliansyah.Â  (2011). Metodologi Penelitian, Prenada Median Grup, Jakarta.Nordin, N. (2011), â€œThe influence of emotional intelligence, leadership behavior and organizational commitment on organizational readiness for change in higher learning institutionâ€, Procedia â€“ Social and Behavioral Sciences, Vol. 29, pp. 129-138.Riaz. (2016). A Study of Impact of Job Stress on Employee Job Satisfaction.Robbins, S. P. (1996). Organizational Behaviour. New Jersey: Prentice Hall, Inc.Robbins, S. P., & Judge, T. A. (2013). Organizational Bahviour Fifteenth Edition. Pearson Education, Inc.Robbins, S. P., & Judge, T. A. (2014). Essentials of Organizational Behavior. NewYork: Pearson Education, Inc.Saleem, R., Mahmood, A., & Mahmood, A. (2010). Effect of Work Motivation on Job Satisfaction in Mobile Telecommunication Service Organizations of Pakistan. International Journal of Business and Management vol. 5, No. 11.Schermerhorn. (2002).Â  Management, 7thed New York: John Wiley & Sons Inc.Shurbagi. (2013). The Relationship between Organizational Commitment and Job Satisfaction in National Oil Corporation of Libya.Sondenaa. (2015). A Study of Job stress, burnout and job satisfaction in staff working with people with intellectual disabilities: community and criminal justice care.Suma, S. (2013). Job Satisfaction and Organizational Commitment: The Case of Shkodra Municipality.Suilstyo, J. (2010). 6 Hari Jago SPSS 17. Yogyakarta: Cakrawala.Wani, D. S. (2013). Job stress and its impact on employee motivation: a study of select commercial bank. International Journal of Business and Mangement Invention, 13-18.Yeh, Y. (2014), â€œExploring the impacts of employee advocacy on job satisfaction and organizational commitment: case of Taiwanese airlinesâ€, Journal of Air Transport Management, Vol. 36, pp. 94-100.Â Â Â